Психологические особенности формирования конфликтологической компетентности у педагогов - Рустамова Сурайё Шахобовна (Academia One, 2026)
The article analyses the nature and content of conflicts arising in the educational environment between its subjects. The phenomenon of conflict competence discussed in the article is presented as a priority personal trait of a teacher, allowing them to interact productively with other subjects of the educational process and build a trajectory of constructive dialogue on a non-conflict basis.
Keywords: conflict; teacher; student